Organic field-effect transistors - Bao, Zhenan; Locklin, Jason John (Optical science and engineering (CRC Press) ;, 2007)
Using a multidisciplinary approach, this text describes the physical understanding of charge transport in single-crystal devices, small molecule oligomers, and conjugated polymer devices.